Development of P/M processing for superplastic aluminium-lithium matrix composites - Koh, Lian Huat. (2009)
This investigation involved the development of a powder metallurgical (P/M) route consisting of, powder mixing, degassing, cold isostatic pressing (CIP) and hot extrusion, for the production, principally, of a 0.8um SiCp reinforced aluminium-lithium 8090 alloy composite. Other particle sizes of reinforcement were also studied ( together with varying volume fractions (Vf) of reinforcement (0.08, 0.16, 0.24). Various wet and dry mixing techniques were investigated and it was found that dry ball milling gave the optimum homogeneity in the powder blend. Mixing parameters for this technique were optimised. It was found that mixing time had a profound effect on the mixture quality and three distinct stages of mixing involving agglomeration, good mixing and de-mixing were identified.